A framework for studying Transformative Experiences through VR - Stepanova, Ekaterina; Quesnel, Denise; Kitson, Alexandra; Prpa, Mirjana; Aguilar, Ivan; Riecke, Bernhard E. (23rd Annual CyberPsychology, CyberTherapy & Social Networking Conference, 2018)
Our view of the world forms based on our experiences. Certain experiences can have a strong powerful effect that could transform an individual’s worldview. These experiences are often described as transformative, or in strong cases, pivotal. Such experience can occur when an individual witnesses a powerful natural phenomenon, such as a vast ocean or mountain views, underwater world, or the view of the Earth from space. After admiring the beauty of the world, individual sometimes experience a shift in their consciousness, and adjust their worldview based on the newly received perspective. Such experiences are profoundly positive, but unfortunately very rare and private, and thus difficult to study or reproduce. We are presenting a framework that suggests a method of studying transformative experience through the use of Virtual Reality (VR) technology. The immersive powers of virtual reality can “teleport” the immersant from the lab into a different world, thus providing the researchers with a unique real-time access to these inherently private emotional experiences in a controlled lab condition (Chirico et al., 2016). In order to understand such complex phenomena we are proposing to describe it as a progression through different stages or levels of the experience, and assess each stage and transition individually. Our framework outlines the progression of the transformative experience in 3 stages: perceptual dissonance, cognitive shift, and behavioral change. The initial stage is a perceptual experience that is presenting a familiar concept, but from a novel perspective, thus creating a perceptual dissonance. Awe-inspiring experiences often share a common characteristic of perceptual vastness (Klatzky et al., 2017), which is arguably impossible to achieve in controlled lab conditions without the use of VR. This stage can elicit emotional responses, such as awe, that can be measured with a use of physiological measures, e.g. goosebumps (Quesnel & Riecke, 2017). After being faced with a perceptual dissonance an individual will have to intake this information, and either accommodate it, assimilate it, or reject it (Gaggioli, 2016). If accommodation was successful, the experience would move to the stage of the cognitive shift; the individual’s worldview is altered in order to account for the new experience. This stage can be assessed through implicit measures of attitudes, e.g., implicit association test (Bruni & Shultz, 2010). Transition to the third stage of the behavioral change happens if there was also a dissonance between the new worldview and the individual’s behavior – this process can be explained through the theory of cognitive dissonance (Festinger, 1962). The third stage can be evaluated through observation of behavior both inside VR and after the experience. To illustrate this framework in a specific context we will look at a VR experience design inspired by the Overview Effect – the profound feeling experienced by astronauts observing the vastness and beauty of the Earth from space, that results in a cognitive shift of increased feeling of connectedness and consequently increased pro-social and pro-environmental behavior (White, 1998). Through an iterative design of a the VR experience, and the use of this framework to assess the progression of a transformative experience, we will be able to identify the key characteristic and triggers in the VR experience that facilitate the progression between the stages of the transformative experience. Understanding how to design for transformative experience in VR will make such profound transformative experiences more accessible both for the researchers interested in studying them as well as for the general public wishing to improve their well-being. References: Bruni, C. M., & Schultz, P. W. (2010). Implicit beliefs about self and nature: Evidence from an IAT game. Journal of Environmental Psychology, 30(1), 95-102. Chirico, A., Yaden, D. B., Riva, G., & Gaggioli, A. (2016). The potential of virtual reality for the investigation of awe. Frontiers in psychology, 7. Festinger, L. (1962). A theory of cognitive dissonance (Vol. 2). Stanford university press. Gaggioli, A. (2016). Transformative experience design. Human Computer Confluence. Transforming Human Experience Through Symbiotic Technologies, 96-121. Klatzky, R. L., Thompson, W. B., Stefanucci, J. K., Gill, D., & McGee, D. K. (2017). The Perceptual Basis of Vast Space. Psychonomic Bulletin & Review, 1-9. Quesnel, D., & Riecke, B. E. (2017). Awestruck: Natural Interaction with Virtual Reality on Eliciting Awe (pp. 205–206). In IEEE Symposium on 3D User Interfaces, Los Angeles, CA, USA White, F. (1998). The Overview Effect: Space Exploration and Human Evolution. AIAA.
Keywords: Riecke; Riecke_2018; alex-kitson; awe; bernhard-riecke; conferenceTalksWithoutPaper; denise-quesnel; ivan-aguilar; katerina-stepanova; mirjana-prpa; symposium; talkWithoutPaper; transformative-experiences